Algorithm of physical rehabilitation of athletes in polyclinic stage of treatment of osteochondrosis - MAKAROVA, E. V.; VASYLIEVA, I. V. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose: develop an algorithm which improves the physical rehabilitation of athletes with osteochondrosis on polyclinic stage of treatment. Material: processed of scientific literature and Internet. Results: this research analyzes traditional recovery of athletes with spinal osteochondrosis on polyclinic stage of treatment. The practical and clinical study showed that etiopathogenesis injuries and diseases of the musculoskeletal system of athletes of different specialties have similar evidences. Therefore, a recovery of sports working capacity during medical rehabilitation treatment does not differ from ordinary patients. We propose an algorithm of physical rehabilitation, aimed for the fast recovery of health of athletes and return them to the athletic training, and conducting therapeutic exercises with specific objects such as balancing disk and preventive "Osan". Conclusions : established that the physical rehabilitation of athletes at polyclinic stage of treatment similar to the rehabilitation of patients non-athletes, and improved algorithm for the physical rehabilitation of athletes with osteochondrosis in the polyclinic stage of treatment.